Estética epistémica: el arte como representación (2018)
The conceptual tool “episteme” erected in the first period of Michel Foucault’s thought, allows to perform an analytic of art from the rules of discursive formation, which displace the traditional treatments that evoke the “mentality” or “conscience” of individuals. Foucault distinguishes three epistemological components in his examination of Western society: The Renaissance, the Classical and the Modern. His analysis of Las Meninas provides elements to show the emergence of the classical episteme that revolves around representation and not about the similarity that characterized the Renaissance episteme. Don Quixote presents himself to Foucault as the hinge between the Renaissance and the classic episteme when he searches for words in things.